Strengthening Regional Agriculture Exports from APEI+ Countries to Mauritius and Seychelles - World Bank Group (World Bank, Washington, DC, 2020)
APEI member countries and Madagascar (APEI ) identified enhanced regional agricultural trade as a key priority. The matter was referred to the World Bank for further analysis which is presented in this report. Potential for increased agricultural exports from APEI+ countries to Mauritius and Seychelles does exist but is smaller than headline numbers suggest. Approximately US$100 million in untapped potential is hampered by high regional transport cost and unlikely to materialize soon. An additional US$35 million of untapped trade potential is in products with high sanitary and phytosanitary (SPS) risks, which pose a serious, though not insurmountable obstacle to regional trade. Among the remaining US$110 million in untapped potential are products such as pulses, nuts and seeds, honey, and dried chili pepper that are less affected by high transport costs and SPS risks.